“Bones in the Medulla Oblongata?”—A Case Report of Intracranial Teratoma and Review of the Literature - Zhang, Xu; Wang, Hongxiang; Hong, Fan; Xu, Tao; Chen, Juxiang (Frontiers in Pediatrics, 2021)
Teratoma in the medulla oblongata is extremely infrequent and has been rarely reported. Severe and sustained brain stem compression resulting from these granitic tumors may cause potentially fatal impairment. Here, we reported a novel case of teratoma that occurred in the medulla oblongata. This 15-year-old boy suffered from a progressive gait disturbance and weakness of limbs for nearly 13 years. Magnetic Resonance Imaging (MRI) revealed an unusual mixed mass in the medulla oblongata and C1-2 spine, which was confirmed as mature teratoma by histopathological examination. Then, surgical resection was performed, followed by postoperative continuous rehabilitation. After a period of rehabilitation, this patient is currently able to mobilize with sticks. No signs of local recurrence occurred. Conclusively, surgical removal is still the preferred treatment for teratoma.